PENGARUH PEMANFAATAN POJOK BACA TERHADAP MINAT BACA DAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SEKOLAH DASAR - Palestin, Balqis Tsuroyya; Cunandar, Dadang (Universitas Muria Kudus, 2024)
The study aims to explore the influence of the School Literacy Movement, through the use of reading corners, on the reading interests and reading abilities of class V students in that school. In the advancing information and technology age, reading skills have become a vital skill. Reading Corner is one of the implementations of the School Literacy Movement that provides easy access for students to acquire and read various kinds of reading materials. This type of research is conducted through a quantitative approach to descriptive methods with the design of research Ex-Post-Facto. The population used in this study is the entire student population in V grade, which is a total of 24 students. The research data was collected through questionnaire instruments and tests, then analyzed using appropriate statistical techniques. The result of this study is that there is an influence of the use of reading corners on student reading interests, but there is no influence on the ability of students to read and understand. The researchers found that there are other factors that can affect the interests of students in reading and understanding. The results are expected to give a deeper understanding of the impact of the utilization of read corners on reading interest and reading ability in V grade students in Elementary School 3 Pagerageung.